Assessment of threedimensional model generated using digital close-range photogrammetric method for heritage documentation applications / Ismail Ma’arof - Ma'arof, Ismail (Institute of Graduate Studies, 2017)
Lately, there were a number of photogrammetric techniques developed and utilized in documenting heritage and historical monuments. Reality image based modelling technique has been frequently used to obtain an accurate measurement of the heritage building, monuments and archaeological site studies. This is in line with the current rapid changes in the development of technology. The subject, which is the heritage and historical monument, is chosen to improve the documentation process. Perhaps with this research, it will give a new drive or tools of improvement for heritage monument documentation projects in Malaysia. It is hoped that the preservation and conservation activities would be developed for the benefit of our future generation. With the enhancement and advancement of instrument being utilized and used during the historical monument documentation, it has been shown that a great number of research and studies have been done by previous researchers. This research aims to assess the 3D reconstruction model obtained from a low-cost, low-specification digital camera, in order to resolve current limitations and gaps for developing 3D models of heritage monument remains using monoscopic close-range photogrammetry image based data. Lower specification for this research is defined as having a resolution of less the state-of-the art digital camera (10-24 Megapixels). The main objective of this research is to carry out a wider investigation into current approaches used in digital documentation of heritage monuments remains. Secondly, to provide a solution for the state-of-the-art image modeling by using low cost, low specification...